Design of magnetic traps for neutral atoms with vortices in type-II superconducting microstructures - Zhang, B. (2014)
We design magnetic traps for atoms based on the average magnetic field of vortices induced in a type-II superconducting thin film. This magnetic field is the critical ingredient of the demonstrated vortex-based atom traps, which operate without transport current. We use Bean’s critical-state method to model the vortex field through mesoscopic supercurrents induced in the thin strip. The resulting inhomogeneous magnetic fields are studied in detail and compared to those generated by multiple normally conducting wires with transport currents. Various vortex patterns can be obtained by programing different loading-field and transport-current sequences. These variable magnetic fields are employed to make versatile trapping potentials.